Validation of aortic valve calcium quantification thresholds measured by computed tomography in Asian patients with calcific aortic stenosis. (25th June 2021) - Guzzetti, Ezequiel; Oh, Jin Kyung; Shen, Mylène; Dweck, Marc R; Poh, Kian Keong; Abbas, Amr E; Mando, Ramy; Pressman, Gregg S; Brito, Daniel; Tastet, Lionel; Pawade, Tania; Falconi, Mariano Luis; et al.
Abstract: Aims: Sex-specific thresholds of aortic valve calcification (AVC) have been proposed and validated in Caucasians. Thus, we aimed to validate their accuracy in Asians. Methods and results: Patients with calcific aortic stenosis (AS) from seven international centres were included. Exclusion criteria were ≥moderate aortic/mitral regurgitation and bicuspid valve. Optimal AVC and AVC-density sex-specific thresholds for severe AS were obtained in concordant grading and normal flow patients (CG/NF). We included 1263 patients [728 (57%) Asians, 573 (45%) women, 837 (66%) with CG/NF]. Mean gradient was 48 (26–64) mmHg and peak aortic velocity 4.5 (3.4–5.1) m/s. Optimal AVC thresholds were: 2145 Agatston Units (AU) in men and 1301 AU in women for Asians; and 1885 AU in men and 1129 AU in women for Caucasians. Overall, accuracy (% correctly classified) was high and comparable either using optimal or guidelines' thresholds (2000 AU in men, 1200 AU in women). However, accuracy was lower in Asian women vs. Caucasian women (76–78% vs. 94–95%; P < 0.001). Accuracy of AVC-density (476 AU/cm 2 in men and 292 AU/cm 2 in women) was comparable to absolute AVC in Caucasians (91% vs. 91%, respectively, P = 0.74), but higher than absolute AVC in Asians (87% vs. 81%, P < 0.001). There was no interaction between AVC/AVC-density and ethnicity (all P > 0.41) with regards to AS haemodynamic severity. Conclusion: AVC thresholds defining severe AS are comparable in Asian and Caucasian populations, and similar to those proposed in the guidelines. However, accuracy of AVC to identify severe AS in Asians (especially women) is sub-optimal. Therefore, the use of AVC-density is preferable in Asians.